2022
DOI: 10.1136/bmj.o2297
|View full text |Cite
|
Sign up to set email alerts
|

Recreational use of nitrous oxide

Abstract: Smart legislation, prevention, and harm reduction are required to reduce the risks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Due to the widespread increase in recreational nitrous oxide (N 2 O) use in Europe, this clinical situation has become increasingly common in emergency and neurology departments [18–20]. Although average consumption is challenging to estimate precisely, our cohort revealed considerable weekly N 2 O intakes, reaching up to 20,000 mL per week, resulting in significant neurological damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the widespread increase in recreational nitrous oxide (N 2 O) use in Europe, this clinical situation has become increasingly common in emergency and neurology departments [18–20]. Although average consumption is challenging to estimate precisely, our cohort revealed considerable weekly N 2 O intakes, reaching up to 20,000 mL per week, resulting in significant neurological damage.…”
Section: Discussionmentioning
confidence: 99%
“…referral centers specializing in neuromuscular diseases, underlines the most sensitive elements for quickly differentiating GBS patients from those suffering from N 2 On. While these two acute sensorimotor neuropathies exhibit significant clinical differences, the occurrence of ambiguous phenotypes (24.1% of N 2 On patients in our cohort) and the broad phenotypic spectrum of GBS compelled us to analyze biological and electrophysiological biomarkers to effectively distinguish between these two disorders.Due to the widespread increase in recreational nitrous oxide (N 2 O) use in Europe, this clinical situation has become increasingly common in emergency and neurology departments[18][19][20].Although average consumption is challenging to estimate precisely, our cohort revealed considerable weekly N 2 O intakes, reaching up to 20,000 mL per week, resulting in significant neurological damage. Given the rapid onset of clinical signs and severe peripheral neurological involvement, GBS was the primary differential diagnosis upon admission for most patients[17].Interestingly, despite all patients eventually admitting their N 2 O use, 22% of N 2 On patients initially concealed it during their first medical interview.Our study on a large cohort firstly allowed us to identify the most prevalent clinical signs in the N 2 On group, thereby delineating a typical clinical picture for N 2 On.…”
mentioning
confidence: 91%
“… 9 N 2 O remains legal to buy in the UK although this is now under review 10 not least due to recent media concern about the increase in chronic abuse, 11 and the alarming increase in use reported in the Netherlands, which has led it to plan for formal controls in 2023. 12 Consuming N 2 O directly from the canister is dangerous—the pressure (~200 kPa) can cause barotrauma, 13 and the temperature of the gas near the outlet (−55°C 14 ) can cause frostbite injuries. 15 Instead, the gas is typically transferred into balloons via either the whipped cream dispenser or a secondary device (creamers or crackers) easily available that can dispense the canister gas into balloons inserted over the device spout.…”
Section: Introductionmentioning
confidence: 99%
“…By 2019, this had risen to 2652 incidents, only to be nearly doubled again by 2021 (4860 incidents) (Advisory Council on the Misuse of Drugs, 2023; van Hulzen, 2019van Hulzen, , 2021. In the United Kingdom, another leading country regarding recreational N 2 O use (lifetime prevalence 4.5%; (Sumnall, 2022)) (Winstock et al, 2015), limited data are available regarding traffic incidents related to N 2 O use. However, one review of incidents in the city center of Manchester demonstrated an increase in N 2 O related traffic incidents, increasing from 31 incidents in 2020 to 71 incidents in 2021 (Advisory Council on the Misuse of Drugs, 2023).…”
Section: Introductionmentioning
confidence: 99%